A Mobile Schwannoma of the Cervical Spinal Cord: Case Report and Review of the Literature. Issue 1 (18th August 2015) - Terada, Yukinori; Toda, Hiroki; Yokote, Akiyoshi; Iwasaki, Koichi
Abstract: BACKGROUND AND IMPORTANCE: Mobile schwannomas have been reported in the lumbar spine and occasionally in the thoracic spine. However, to the best of our knowledge, this is the first known report of a cervical mobile schwannoma. Mobile schwannomas require careful preoperative and intraoperative evaluation of their localization because tumor mobility may result in surgery at the wrong level. CLINICAL PRESENTATION: A 68-year-old man had complained of clumsiness in his left hand for 10 years. An initial magnetic resonance image (MRI) showed an intradural extramedullary tumor at the C5 to C7 levels, deformation of the adjacent spinal cord, and unusual dilatation of the subarachnoid space from the C7 to T1 levels. A subsequent MRI revealed that the tumor had moved to the C6 to T1 levels. We diagnosed the lesion as a mobile tumor of the cervical spinal cord. The patient underwent a C6-C7 laminectomy with an additional partial laminectomy of C5 and T1. Intraoperative ultrasonography helped localize the tumor. Transdural ultrasonography and direct observation confirmed the tumor mobility. The tumor was completely removed. The histological diagnosis was schwannoma. CONCLUSION: We observed an extremely rare case of a mobile schwannoma of the cervical spine. Unusually dilated subarachnoid space adjacent to the tumor can be a diagnostic sign of tumor mobility, regardless of vertebral level. Repeated MRI studies are useful to preoperatively confirm tumor mobility. Intraoperative ultrasonography is valuable for the real-time localization of such mobile tumors to avoid potentially performing surgery at the wrong vertebral level.